2023
DOI: 10.1039/d3tc01028g
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional pseudohalide-based ionic liquid doping promotes efficient and stable perovskite solar cells

Abstract: High-quality perovskite film is crucial to realizing high-efficiency stable perovskite solar cells. Doping is a direct and effective strategy to passivate defects and improve the crystal quality of perovskite films....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…44 Interestingly, the peak of P–F also shifted from 840.8 cm −1 to 832.6 cm −1 , which suggested that P–F can also interact with PbI 2 . 45 It is inferred that BMIMPF 6 could interact with the uncoordinated Pb 2+ to passivate the defects. Then, steady-state photoluminescence (PL) was measured to confirm the passivation effect of BMIMPF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…44 Interestingly, the peak of P–F also shifted from 840.8 cm −1 to 832.6 cm −1 , which suggested that P–F can also interact with PbI 2 . 45 It is inferred that BMIMPF 6 could interact with the uncoordinated Pb 2+ to passivate the defects. Then, steady-state photoluminescence (PL) was measured to confirm the passivation effect of BMIMPF 6 .…”
Section: Resultsmentioning
confidence: 99%
“…102 As a result, the modified PSCs achieved a PCE of 24.4% and retained over 90% of their initial efficiency under 60–70 °C for 1900 h. Recently, Guo et al introduced the multifunctional IL tetraethylammonium hexafluorophosphate (TEAPF 6 ) as an additive into the perovskite film. 103 It was found that the PF 6 − can enhance the crystal structure and passivate the defects in the perovskite film by bonding with uncoordinated Pb 2+ and the organic cation and filling the halide vacancies, which helps to suppress the ion migration and charge recombination in the perovskite film. They still further characterized the effect of the TEAPF 6 additive on the crystal quality of perovskite films by X-ray diffraction (XRD).…”
Section: Additivesmentioning
confidence: 99%
“…S12 (ESI†) shows the dark J – V curves of original and HA-doped PSCs, proving that the HA-doped PSC exhibits a very small leakage current, as a result, reducing charge recombination loss and ensuring high V OC and fill factor (FF) of the device, and improving the efficiency of the device. 26–28 To better understand the charge transport and recombination in the PSCs, we also obtained the open-circuit photovoltage attenuation curves and derived the carrier lifetime plots in Fig. S13 (ESI†).…”
mentioning
confidence: 99%